Intellectual capital efficiency and firm performance: a study of listed manufacturing companies in sri lanka - Aravinth, S.; Sritharan, V. (International Conference on Contemporary Management [ICCM]-2021, 2021)
Intellectual capital and knowledge are foremost thing of new economic system is increasing every day. The purpose of this research is to examine the impact of Intellectual capital efficiency on firm performance and to examine the relationship between the intellectual capital efficiency and financial performance by using data drawn from 32 manufacturing companies listed in Colombo Stock Exchange Sri Lanka over the five years period from 2015 to 2019. Value added intellectual coefficient (VAIC) approach developed by Ante Pulic is used to determine intellectual capital efficiency (ICE). According to that, human capital efficiency (HCE) and structure capital efficiency (SCE) are used as intellectual capital efficiency proxies of this research. Return on equity is used to measure the financial performance of selected manufacturing companies. The data obtained from manufacturing companies' annual reports are regressed to measure the impact of Intellectual capital efficiency on firm performance and correlated to identify the relationship between intellectual capital efficiency and firm performance. Findings from the regression analysis of this research indicates that intellectual capital efficiency has significant 2 impact on firm performance (r = 0.32) in case of human capital efficiency (0.031). At the same times intellectual capital efficiency in case of human capital efficiency has significant positive correlation (0.56) with financial performance. Further, findings of this study reveal that, the important of intellectual capital efficiency especially in human capital efficiency as a key factor that can enhance a company's ability to maintain their competitive position in manufacturing companies, Sri Lanka.
Keywords: Financial performance; Intellectual capital efficiency; Manufacturing companies